Respiratory support in patients with severe COVID‑19 in the International Severe Acute Respiratory and Emerging Infection (ISARIC) COVID‑19 study: a prospective, multinational, observational study - Reyes, Luis Felipe; Murthy, Srinivas; Garcia-Gallo, Esteban; Merson, Laura; Ibáñez-Prada, Elsa D.; Rello, Jordi; Fuentes, Yuli V.; Martin-Loeches, Ignacio; Bozza, Fernando; Duque, Sara; Taccone, Fabio S.; Fowler, Robert A.; et al. (Springer Nature, 2022)
Background Up to 30% of hospitalised patients with COVID-19 require advanced respiratory support, including high-flow nasal cannulas (HFNC), non-invasive mechanical ventilation (NIV), or invasive mechanical ventilation (IMV). We aimed to describe the clinical characteristics, outcomes and risk factors for failing non-invasive respiratory support in patients treated with severe COVID-19 during the first two years of the pandemic in high-income countries (HICs) and low middle-income countries (LMICs).